TRANSPLANTASI KARANG TRANSPLANTASI KARANG DAN RENCANA MONITORING DI TITIK PENYELAMAN MOKOTAMBA PULISAN, PADA DESTINASI SUPER PRIORITAS, LIKUPANG - Lagarense, Bet El Silisna; Pesik, Mex Usmeny; Rauf, Fitriani Fiany; Gumolili, Youdy Joseph Hendrik (HOSPITALITI DAN PARIWISATA, 2024)
This research aims to determine the growth rate and survival rate of coral fragments transplanted into plant media in the Mokotamba Pulisan area, North Sulawesi. Determination of the location for planting media is carried out based on the results of observations in the field. The method used is the frame method, where naturally broken coral fragments are attached to sondo-shaped pieces of iron, with each fragment transplanted facing the direction of the incoming sunlight. The initial research results were carried out by measuring the initial length of coral fragments in each unit of planting media and will then be measured periodically every four months to obtain the growth rate and survival rate of transplanted coral fragments. Key words: coral transplantation, monitoring, conservation, Mokotamba, Likupang, Indonesia